Ultimate rockopedia : the most complete rocks & minerals reference ever - Tomecek, Steve (National Geographic kids., 2020)
Presents a full-color illustrated guide to the Earth's rocks and minerals that offers information on their types, formation, uses, and characteristics. Includes an interview with a geologist, a glossary of terms, and extensive resources for further study.